The effect of leverage, growth, and company size on earnings management in mining companies listed on the Indonesia Stock Exchange from 2020 to 2024 - Hanifah, Siti; Fathihani, Fathihani (Enrichment : Journal of Management, 2025)
Financial statements play a crucial role in reflecting a company’s financial health; however, they are often subject to manipulation through earnings management to meet stakeholder expectations. This study aims to analyze the effect of leverage, company growth, and company size on earnings management in mining companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The study employs a quantitative causal research design using secondary data from 19 mining companies selected through purposive sampling, resulting in 95 firm-year observations. Earnings management is measured using discretionary accruals calculated with the Modified Jones Model (MJM). Data were analyzed using multiple linear regression with classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The results show that leverage and company growth have a significant positive effect on earnings management, while company size has no significant effect. These findings suggest that higher debt ratios and rapid company expansion encourage managerial tendencies to manipulate earnings to maintain financial stability and investor confidence. Conversely, firm size does not influence such practices, possibly due to stricter oversight and higher transparency requirements in larger firms. The study provides empirical support for agency theory, emphasizing the role of financial pressure in shaping managerial behavior. Practically, it highlights the importance of improving governance mechanisms and monitoring systems to minimize opportunistic financial reporting practices in the mining sector.